Sunni Communities in the Islamic Republic of Iran, 2013-2021 : Securitization, Secularization and Privatization - Doroh, Hessam Habibi, (Middle East and Islamic Studies E-Books Online, Collection 2023., 2023)
Sunni-Shia relations in Iran offer an analytical guide for the interpretation of inequality, securitization, and immigration. This book reorients our understanding of contemporary Iran by answering still unacknowledged questions: how is the relationship, the interaction and socio-political behaviour between the Islamic Republic and its Sunni minorities? Using unexamined sources and fieldwork, Hessam Habibi Doroh shows a clear insight into the life of Iranian Sunnis, their contention and cooperation with the state during Hasan RouhaniÂ´s presidency. Comparison with the wider region complements this nuanced portrayal of impacts of privatization, secularization, and securitization on the sectarian relations between the state and its minorities. .